Anemia falciforme: crises vaso-oclusivas parecem estar relacionadas à redução da concentração de proteínas na membrana eritrocitária - Araújo, Iara Veras de (2015)
Sickle cell anemia is a common genetic disorder resulting from a specific change in position six of the hemoglobin gene, which results in different alleles, which when transcribed, codes for hemoglobin S which leads to the formation of sickle erythrocytes. Red blood cells containing hemoglobin S acquire in hypoxic conditions, the sickle-shaped, causing vaso- occlusive crisis in patients. This study aimed to isolate erythrocyte membrane proteins of patients with sickle cell anemia (in symptomatic and asymptomatic stages) and to correlate changes identified in these periods, using High Performance Liquid Chromatography (HPLC - ion exchange), SDS-PAGE (1D and 2D) and Mass Spectrometry (MS-ESI)). Was performed proteomic analysis in erythrocyte membrane proteins obtained from peripheral blood samples from three patients, collected over two years, and separated according to the presence (PC) or absence of vaso-occlusive crisis (PSC) at the time of collection. The control group consisted of two individuals with no diagnosis of hemoglobinopathies. We identified the presence of a higher concentration of membrane proteins in sickle cell erythrocytes, particularly in CSP patients and showed that during attacks the amount of protein present in the erythrocyte membrane of patients undergoes reduction (20.7% -PC1; 34 2% - PC3 and 45.2% - PC2). Among the 159 membrane proteins extracted from sickle cell erythrocytes, 148 were identified and 11 were not identified, using as parameter the database ExPASy TagIdent. Among the proteins not identified, six were extracted from the plasma membrane of PC patients and five PSC patients. The identification of PRDX2 protein (peroxiredoxin with an apparent molecular mass of 41 kDa) with an apparent molecular weight below 30 kDa, suggesting the structural change of this protein. Failure to identify 11 proteins extracted membrane of sickle cell erythrocytes suggests quantitative changes in protein expression of these patients. Our results also suggest that the vaso-occlusive crises may be related to a reduction in total protein concentration of the erythrocyte membrane in patients.